2016
DOI: 10.1039/c6ob02221a
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective synthesis of 3-acetoxy-4-(3-aryloxiran-2-yl)azetidin-2-ones and their transformation into 3,4-oxolane-fused bicyclic β-lactams

Abstract: cis-3-Acetoxy-4-(3-aryloxiran-2-yl)azetidin-2-ones were prepared through a Staudinger [2+2]-cyclocondensation between acetoxyketene and the appropriate epoxyimines in a highly diastereoselective way. Subsequent potassium carbonate-mediated acetate hydrolysis, followed by intramolecular ring closure through epoxide ring opening, afforded stereodefined 3-aryl-4-hydroxy-2-oxa-6-azabicyclo[3.2.0]heptan-7-ones as a novel class of C-fused bicyclic β-lactams. Selective benzylic oxidation of bicyclic N-(4-methoxybenzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…The introduction of the epoxide was realized prior resulted in deprotected β-lactams 12d/13d in low to moderate yield (Scheme 3). The relative stereochemistry of major diastereomers 12 could be deduced based on the vicinal coupling constants between the C3 and C4 protons of the β-lactam core, the protons of C1 0 and C2 0 of the oxirane moiety, and the protons of C4 and C1 0 in 1 H NMR (CDCl 3 ), which are in agreement with the values reported in the literature for similar β-lactams (Figure 1) [5,7].…”
Section: Resultssupporting
confidence: 88%
“…The introduction of the epoxide was realized prior resulted in deprotected β-lactams 12d/13d in low to moderate yield (Scheme 3). The relative stereochemistry of major diastereomers 12 could be deduced based on the vicinal coupling constants between the C3 and C4 protons of the β-lactam core, the protons of C1 0 and C2 0 of the oxirane moiety, and the protons of C4 and C1 0 in 1 H NMR (CDCl 3 ), which are in agreement with the values reported in the literature for similar β-lactams (Figure 1) [5,7].…”
Section: Resultssupporting
confidence: 88%
“…The solution was concentrated under reduced pressure and the pure epoxy aldehyde was isolated by column chromatography (SiO 2 , 10–20% EtOAc in hexane). The 1 H NMR spectrum for each epoxide was consistent with the literature values (see Supporting Information) for (±)-3-phenyloxirane-2-carbaldehyde ( 6a ), (±)-3-pentyloxirane-2-carbaldehyde ( 6b ), (±)-3-((benzyloxy)­methyl)­oxirane-2-carbaldehyde ( 6c ), and (±)-3-((benzyloxy)­methyl)­oxirane-2-carbaldehyde ( 6d )…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Phosphonate 16a (0.25 g, 0.45 mmol) was reacted as above to give phostone 17a as a paleyellow oil (0.154 g, 67%): IR (neat) 2919, 2850, 1248 cm −1 ; 1 H NMR (CDCl 3 ) δ 7.39−7.28 (m, 5H), 4.55 (q, J HH = 11.7 Hz,2H),4.33 (m,1H),4.13 (m,2H),3.81 (m,2H),3.64 (m,1H) 3.53 (m,2H),3.25 (m,1H),2.37 (m,1H), 2.05 (m, 1H), 1.78 (m, 2H), 1.52 (m, 2H), 1.29 (m, 27H), 0.88 (t, J HH = 6.9 Hz, 3H); 13 C{ 1 H} NMR (CDCl 3 ) δ 138. 0,128.5,127.9,127.8,81.2 (d,J CP = 7.3 Hz),77.6,77.2,76.8,73.7,70.7,70.6,69.4 (d,J CP = 6.8 Hz), 60.9 (d,J CP = 6.4 Hz),32.0,29.9,29.8,29.8,29.7,29.6,29.5,26.4,24.7 (d,J CP = 7.9 Hz),22.8,17.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…14 The corresponding epoxide 4e could be conveniently prepared from 3a and m-CPBA in good yield. 15 Control experiments (eqs 1 and 2 in Scheme 5) showed that the reaction could not occur in the absence of P1 or PhSiH 3 . If the reaction was stopped at 1 h (eq 3 in Scheme 5), 4f was obtained in 73% yield and 3a in 9% yield.…”
mentioning
confidence: 99%
“…Treatment of 3a with hydroxylamine in n -BuOH at 80 °C for 8 h led to oxime 4d . The corresponding epoxide 4e could be conveniently prepared from 3a and m -CPBA in good yield …”
mentioning
confidence: 99%